Exceptional response to alectinib for duodenal carcinoma with ALK fusion: A case report and literature review - Isaka, Yuri; Sasaki, Akinori; Saito, Akira; Motomura, Yasuaki; Ando, Yayoi; Nakamura, Yoshiaki (Frontiers in Oncology, 2023)
Patients with advanced duodenal carcinoma usually have a poor prognosis due to limited effective chemotherapy options. The study for genotype-directed therapy in patients with duodenal carcinoma is progressing. However, no clinical data assessing the efficacy of molecularly targeted therapy are presently available. We report the case of a 64-year-old woman who was diagnosed with anaplastic lymphocyte kinase (ALK) fusion-positive advanced duodenal carcinoma. Echinoderm microtubule associated protein like-4 (EML4)-ALK rearrangement was detected by comprehensive genomic profiling after resistance to first-line chemotherapy. The patient received alectinib, an ALK inhibitor, with marked shrinkage in primary tumor and liver metastases. She is currently being treated with alectinib for 6 months or more. This is the first report of the efficacy of alectinib in a patient with duodenal carcinoma harboring ALK fusion. Additionally, this case report suggests that the practical use of next-generation sequencing may expand optimal treatment choices in rare solid tumors, including duodenal carcinoma.